Instilling Moral Values in Teenage Victims of Broken Homes by Family Guidance - Sitti Khotijah; Alfira Aghnia (Penerbit Hellow Pustaka, 2025)
Moral values ​​are a measure of a person's attitude and behavior, can be measured from good or bad attitudes and right or wrong. A person will be said to be moral when in behaving he has good ethics and does not violate the norms that apply in his environment. Behaving of course should not be arbitrary and careless, there must still be a measure in every attitude that we carry out because basically morals are a benchmark for our behavior in society. Broken home is where the family cannot be reunited or is called divorce, this divorce is where parents no longer care about the messy home situation that can cause children to have problems both at home, at school and in the community. Family guidance is an approach that can be used by counselors to provide assistance to a family through interaction between members so that the family can overcome the problems it faces for the welfare of family members as a whole with the aim of achieving a harmonious family. In this study, the problem studied is how family guidance in instills moral values ​​to adolescent victims of broken homes, and how the implications of these moral values ​​​​are on the lives of adolescent victims of broken homes and the purpose of this study is to find out how family guidance in instills moral values ​​​​to adolescent victims of broken homes and how the implications of these moral values ​​​​are on the lives of adolescent victims of broken homes. This study uses a qualitative research method, qualitative research is observing people in the environment, interacting with them and interpreting their opinions related to the world around them. This type of research is a case study research. Based on the description that has been presented by the researcher, it can be concluded: 1. Family guidance in instilling moral values ​​to adolescent victims of broken homes, goes well: increasing children's spirituality, providing positive knowledge, teaching self-adjustment. 2. The implications of these moral values ​​on the lives of adolescent victims of broken homes through the family guidance approach have a very good impact on adolescents, in forming good character and having skills in making good decisions.